Ontological Sovereignty: Black Justifications for Violent Resistance to Slavery, 1500-1900 - Dalitso Ruwe (Journal of Modern Philosophy)
This essay advances the claim that Africana thinkers between the 16th and 19th centuries developed critiques of slavery with the following themes: (a) slavery as a function of ignorance of biblical or secular knowledge; (b) slavery as a function of European carnal impulses; (c) slavery as a crime, for which the God-ordained punishment was death; (d) justification of self-defense to restore African liberty; and (e) economic restitution for stolen labor. This essay focuses on claims to justify self-defense for African liberty.